Innovation and entrepreneurship in Malaysian mobile-phone-applications industry: implications for technology intelligence - Adham, Khairul Akmaliah; Said, Mohd Fuaad; Hanninen, Seppo J.; Walsh, Steven T. (Inderscience Publishers, 2009)
The integration of technology intelligence within an innovation process can significantly contribute to the recognition, development, and exploitation of new business opportunities. In this study, we examined the innovation and entrepreneurship process within small firms in the Malaysian mobile-phone applications industry. The Malaysian mobile-phone industry presents huge opportunities to new businesses, yet its development is hindered by the highly monopolistic telecommunication industry structure and by Malaysia's largely underdeveloped supportive business contexts. It was found that product ideas originated from founders' own perceptive ability and/or interactions with industry experts, and they involved rigorous technology intelligence efforts.